Investigating the Relationship between Expectations Gap from Attitude of Accreditation of Audit Report by Credit Experts and Non-repayment of Granted Facilities in the Branches of Keshavarzi Bank of Iran - Farasangi, Saeid Ebrahimipour; Noghondari, Amirhossein Taebi (International Journal of Economics and Financial Issues, 2017)
The aim of this study is to investigate the relationship between expectations gap from attitude of accreditation of audit report by credit experts and non-repayment of granted facilities in the branches of Keshavarzi Bank of Iran. Considering that collection of debts shows the bank's position in society and the banking network and improve performance of management. Credit officers and experts of banks repeatedly for authentication to borrowers with accuracy in audit reports specially type of comment provided act to the credit assessment of the economic unites of applicant of facilities. The withdrawal of auditors from the accreditation role of independent auditors and withdrawal of users has a significant difference which provide assessments with different aspects to meet the expectations gap from it and in such a situation, experts and officials of credit part of the banks cannot resolve their critical task from society's expectations and this in turn will cause impact on the bank's claims. Results of the survey research are based on results of collecting 250 questionnaires from decision-makers and officials of paying credits in the banking system. In this regard, it is tried to measure this relation by using statistics and data collected in time period 2015. In this study, linear regression is used at 95% confidence level, according to the results, it was specified by increasing expectations gap from attitude of accreditation of audit report by credit experts, non-repayment of granted facilities increases that shows the direct relationship between the two variables. So a systematic and comprehensive program to be designed and implemented to reduce expectation gap from audit report by credit experts so that the ability to analyze audit report and financial statements related to report and correct understanding of the applicant's financial and credit position of facilities to be provided. Keywords: Attitude of Accreditation, Expectations Gap from Audit Report, Credit Experts, Granted Facilities JEL Classifications: C32; O13; O47